2021
DOI: 10.1166/jbn.2021.3170
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Treatment of Colorectal Cancer Using Chlorin e6-Loaded Poly(lactide-co-glycolide)- Based Nanoparticles

Abstract: We prepared poly(lactide-co-glycolide) (PLGA) encapsulated with chlorin e6 (Ce6) in an effort to increase the stability and efficiency of photosensitizers for photodynamic therapy (PDT). We determined that Ce6-loaded PLGA nanoparticles (PLGA-Ce6 NPs) had drug-loading efficiency of 5%. The efficiency of encapsulation was 82%, the zeta potential was- 25 mV, and the average diameter was 130 nm. The encapsulation of Ce6 in PLGA nanoparticles showed excellent stability. The nanoparticles exhibited sustained Ce6 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…To solve these problems, various vehicles such as nanoparticles, polymer conjugates, proteins, polymeric micelles, nanomaterials, and cyclodextrins have been studied [16][17][18][19][20]. Nano-dimensional carriers have various advantages such as long blood circulation, solubilization of hydrophobic drugs, active/passive targeting of tumors, avoidance of reticuloendothelial system uptake, and site-specific delivery of bioactive agents [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To solve these problems, various vehicles such as nanoparticles, polymer conjugates, proteins, polymeric micelles, nanomaterials, and cyclodextrins have been studied [16][17][18][19][20]. Nano-dimensional carriers have various advantages such as long blood circulation, solubilization of hydrophobic drugs, active/passive targeting of tumors, avoidance of reticuloendothelial system uptake, and site-specific delivery of bioactive agents [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Nano-dimensional carriers have various advantages such as long blood circulation, solubilization of hydrophobic drugs, active/passive targeting of tumors, avoidance of reticuloendothelial system uptake, and site-specific delivery of bioactive agents [21][22][23]. For example, Lin et al reported that Ce6-encapsulated poly(lactide-co-glycolide) nanoparticles show sustained drug release properties over 3 days, enhanced cellular uptake against HCT-116 cells, and higher phototoxicity than Ce6 itself [16]. Polymeric micelles are frequently employed for the site-specific delivery of bioactive agents against tumors [22].…”
Section: Introductionmentioning
confidence: 99%
“…In general, success in combining porphyrins and polymers as carriers has been observed in a large number of scientific papers. Systems with polymers such as chitosan [ 21 ], polyethylene glycol [ 22 ], and poly(lactide-co-glycolide) [ 23 , 24 ] are well studied. But special attention should be paid to a polymer such as poly-3-hydroxybutyrate (PHB) [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 In general, success in combining porphyrins and polymers as the carriers is observed in a large number of scientific papers. Systems with polymers such as chitosan [16]; polyethylene glycol [17]; poly(lactide-co-glycolide) [18,19] are well studied. But special attention should be paid to such a polymer as poly-3-hydroxybutyrate (PHB) [20,21].…”
Section: Introductionmentioning
confidence: 99%